Inhibition of Food Intake in Obese Subjects by Peptide YY3–36 - Batterham, Rachel L; Cohen, Mark A; Ellis, Sandra M; Le Roux, Carel W; Withers, Dominic J; Frost, Gary S; Ghatei, Mohammad A; Bloom, Stephen R (The New England journal of medicine, 2003)
The gut hormone peptide YY 3–36 (PYY) has been shown to decrease appetite and caloric intake in subjects of normal weight, but it was not known whether obese people are resistant to PYY, as they are to leptin. In this double-blind, controlled, crossover trial, PYY levels were lower in obese subjects than in lean subjects. Infusion of PYY decreased appetite and food intake in both lean and obese subjects. Infusion of the gut hormone peptide decreased appetite and food intake. Obesity and its associated pathologic features are major causes of illness and death worldwide. In the United States, obesity accounts for 280,000 deaths annually, and at current rates of increase it will supplant smoking as the primary cause of preventable death. 1 However, despite the recognition that even moderate weight loss confers significant health benefits, 2 to date there have been few effective treatments for obesity, although surgery has been shown to be of use in selected patients. 3 We recently showed that infusions of the gut hormone fragment peptide YY 3–36 (PYY) that produced typical naturally occurring postprandial levels reduced 24-hour food . . .